Understanding Smart Growth Savings. Evaluating Economic Savings and Benefits of Compact Development. - Litman, Todd (My University, 2021)
How communities develop can have many direct and indirect impacts. Smart Growth policies create more compact, multi-modal development which reduces per capita land consumption and the distances between destinations. This, in turn, reduces the costs of providing public infrastructure and services, improves accessibility, and reduces motor vehicle travel, which provides many economic, social and environmental benefits. This report examines these impacts. It defines Smart Growth and its alternative, sprawl, summarizes current research concerning their costs and benefits, investigates consumer preferences, and evaluates Smart Growth criticisms.This report should be useful to anybody involved in development policy analysis.
Keywords: Stadtwachstum; Siedlungswachstum; Nachhaltige Stadtentwicklung; Stadtentwicklungsplanung; Infrastrukturplanung; Verkehrsinfrastruktur; Verdichtung; Zersiedelung; Kosten-Nutzen-Analyse; Smart growth